Islam and quantum physics: from signs to science - Akdogan, Cemil (ISTAC, 2012)
The symbolic and mental nature of science that had been divulged for the first time by the Qur'an has also been recognized by quantum physics thirteen centuries later, i.e., in the first decades of the twentieth century. Isl (a) over barm and quantum physics are compatible due to a shared phenomenological approach which denies that we can know the substance of anything or that matter has a substance at all. In other words, both entirely depend on signs ((a) over bary (a) over bart), appearances (phenomena) or symbols that cannot have any substance or corresponding reality as independent, material entities in the external world. It is through the elimination of material substance that human consciousness has gained its pivotal and fundamental position and placed science into its proper place. Although quantum physics does not depend on the unity and oneness of God, such a religious basis can easily be supplied by Islam.